خدمات الضيافة وعلاقتها بالمقاصد التحسينية = Hospitality services and it relationship with maqasid attahsiniyyah - AB Hadi, Asmaa; Zakariyah, Luqman; Zaim, Muntaha Artalim (GBSE, 2017)
Hospitality services are closely related to the Maqasid al-Sharia, especially on the improvement side where significantly reflected in hospitality services provided by some States and institutions in favor of people, due to laws, Islamic values and Maqasid alshari`ah became almost rarely applied in transactions between individuals, thus the need to confirm the importance of Maqasid attahsiniyyah to achieve the interests of the people and maintain the Five of maqasia al-shari`ah, This study seeks to hospitality services relationship with Maqasid attansiniyah by studying the Maqasid of Shari`ah, hospitality services, the relationship between the services and Maqasiad attahsiniyyah, and the importance of those services and some of examples; With Allah`s guide the source of strength